Andrographolide Suppresses the Growth and Metastasis of Luminal-Like Breast Cancer by Inhibiting the NF-κB/miR-21-5p/PDCD4 Signaling Pathway - Li, Junchen; Huang, Lixun; He, Zinan; Chen, Minggui; Ding, Yi; Yao, Yuying; Duan, Youfa; Zixuan, Li; Qi, Cuiling; Zheng, Lingyun; Li, Jiangchao; Zhang, Rongxin; et al. (Frontiers in Cell and Developmental Biology, 2021)
Tumor growth and metastasis are responsible for breast cancer-related mortality. Andrographolide (Andro) is a traditional anti-inflammatory drug used in the clinic that inhibits NF-κB activation. Recently, Andro has been found in the treatment of various cancers. Andro inhibits breast cell proliferation, invasion, and induces apoptosis via activating various signaling pathways. Therefore, the underlying mechanisms regard to the anti-tumor effect of Andro are still need to be further confirmed. Herein, a MMTV-PyMT spontaneous luminal-like breast cancer lung metastatic transgenic tumor model was employed to estimate the anti-tumor effect of Andro on breast cancer in vivo. Andro significantly inhibited tumor growth and metastasis in MMTV-PyMT mice and suppressed cell proliferation, migration, and invasion of MCF-7 breast cancer cells in vitro. Meanwhile, Andro significantly inhibited the expression of NF-κB, and the downregulated NF-κB reduced miR-21-5p expression. In addition, miR-21-5p dramatically inhibited the target gene expression of programmed cell death protein 4 (PDCD4). In the current study, we demonstrated the potential anti-cancer effects of Andro on luminal-like breast cancer and indicated that Andro inhibits the expression of miR-21-5p and further promotes PDCD4 via NF-κB suppression. Therefore, Andro could be an anti-tumor agent for the treatment of luminal-like breast cancer in the clinic.